Leaf Classification using Local Binary Pattern and Histogram of Oriented Gradients - Janahiraman T.V.; Yee L.K.; Der C.S.; Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer vision; Graphic methods; Learning systems; Support vector machines; Classification process; Complex structure; Feature extractor; Histogram of oriented gradients; Leaf classification; Local binary patterns; Medical treatment; Oriented gradients; Classification (of information)